Long-term complications of splenectomy in adult immune thrombocytopenia. Issue 48 (November 2016) - Thai, Lan-Huong; Mahévas, Matthieu; Roudot-Thoraval, Françoise; Limal, Nicolas; Languille, Laetitia; Dumas, Guillaume; Khellaf, Mehdi; Bierling, Philippe; Michel, Marc; Godeau, Bertrand
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The recent large decrease in splenectomy use for chronic immune thrombocytopenia (ITP) is partly due to still-unsolved questions about long-term safety. We performed the first single-center exposed/unexposed cohort study evaluating the long-term incidence of splenectomy complications in patients with primary ITP. Overall, 83 patients who underwent splenectomy more than 10 years ago (exposed) were matched with 83 nonsplenectomized patients (unexposed) on the date of ITP diagnosis ±5 years, age and gender. After a median follow-up of 192 months (range 0.5–528), 43 patients (52%) achieved overall response after splenectomy. Splenectomized patients experienced more venous thromboembolism (VTE) than controls (n = 13 vs n = 2, P  = 0.005). On multivariate analysis, splenectomy was an independent risk factor of VTE (hazard ratio = 4.006, P  = 0.032 [95% confidence interval: 1.13–14.21]). Splenectomized patients presented more severe infections on long-term follow-up: all required hospitalization, and 5/26 (19%) infections led to severe sepsis or septic shock and to death for 3 cases (none in controls). However, the incidence of malignancy was similar in both groups, as was cardiovascular risk, which appeared to be related more to ITP than splenectomy. Finally, splenectomy did not significantly decrease overall survival. Despite the risk of thrombosis and severe sepsis, splenectomy remains an effective and curative treatment for ITP.